2015
DOI: 10.7727/wimj.2013.214
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and Attitudes Toward Medical Professionalism among Students and Junior Doctors in Trinidad and Tobago

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…[ 24 ] A similar report in surveying information and attitudes toward medical professionalism among pre-clinical students demonstrated that there is restricted information but a good attitude toward medical professionalism and formal training, and educational programs must be changed right now. [ 25 ] Present study also found that pre-clinical (phase 1) students showed a good understanding of professionalism by recommending actions for all of the 34 survey statements. According to Velayo et al, [ 26 ] the pre-clinical performance is positively correlated with the clinical success of the medical students.…”
Section: Discussionsupporting
confidence: 60%
“…[ 24 ] A similar report in surveying information and attitudes toward medical professionalism among pre-clinical students demonstrated that there is restricted information but a good attitude toward medical professionalism and formal training, and educational programs must be changed right now. [ 25 ] Present study also found that pre-clinical (phase 1) students showed a good understanding of professionalism by recommending actions for all of the 34 survey statements. According to Velayo et al, [ 26 ] the pre-clinical performance is positively correlated with the clinical success of the medical students.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have shown that the students' attitude toward professionalism had an inverse relationship with their years of study. 15,25 Likewise, in the present study, first-year residents had a higher perception of professionalism than those in the fifth year. According to Salinas-Miranda et al, 26 professionalism values during clinical training are neglected due to environmental and individual challenges.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies also have pointed out that professionalism training should be included in the curriculum of general medicine and residency program as formal training. 14,15 However, a part of these tutorials could be presented in the form of a hidden curriculum. 30,31 This curriculum includes the culture and structure experienced by residents in a clinical education environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] A similar study in assessing knowledge and attitudes toward medical professionalism among students and junior doctors showed that there is limited knowledge but good attitude toward medical professionalism and formal training, and educational programs must be revised in this regard. [20] …”
Section: Discussionmentioning
confidence: 99%